Dampak Persepsi Nilai, Merek, Store Atmosphere dan Harga terhadap Minat Pembelian pada Supermarket Berastagi - Putri Yuliani Rambe; Ade Parlaungan; Pitriyani Pitriyani (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of Perceived Value, Brand, Store Atmosphere, and Price on Purchase Intention at Supermarket Berastagi. This research uses a quantitative approach with a descriptive method. Data were collected through a questionnaire distributed to 100 respondents who are consumers of Supermarket Berastagi. The data analysis technique used is Structural Equation Modeling (SEM) based on SmartPLS. The results show that the variable Perceived Value (X1) has a positive and significant impact on purchase intention, the variable Brand (X2) has a positive and significant impact on purchase intention, the variable Store Atmosphere (X3) has a positive and significant impact on purchase intention, and the variable Price (X4) has a positive and significant impact on purchase intention.